The COVID-19 pandemic and the incidence of acute coronary syndromes at General Hospital of Veroia - Sdogkos, Evangelos; Roditis, Pavlos; Papadopoulos, Antonios; Spahiu, Anila; Aidinis, Andreas; Pliatsika, Maria; Vogiatzis, Ioannis (Health & Research Journal, 2024)
Background: Although deaths from Acute Coronary Syndromes (ACS) are the most prevalent globally, during the outbreak of the new SARS-CoV-2 coronavirus pandemic, there was a declining trend in hospital admissions for ACS patients. Inevitably a reduction of invasive procedures in cardiac catheterization laboratories was observed. Moreover, an increase in sudden out-of-hospital cardiac deaths was recorded. On the other hand, patients that eventually treated in the hospital had a much worse outcome in terms of cardiac function. Inadequate treatment of acute myocardial infarction resulted in a further increase in mortality due to coronary artery disease. The aim of our study was the comparison of admissions of the patients with ACS before and during the COVID-19 pandemic. Methods: A retrospective single center study was conducted. We recorded all admissions with ACS underwent invasive interventions during the period of lockdown due to COVID-19 pandemic, in Greece, from 16 March 2020 to 1 May 2020 (study period A), as well as in the period of gradual withdraw of restrictions from 2 May 2020 to 1 June 2020 (study period B),. The data were compared with those of the periods of 2019 (control period A and B). Results: One hundred thirty eight patients were the group of study period and 158 were the group of the control period. The reduction rate was 12.7% in study period. The largest decrease in admissions concerned with elderly patients over 75 years old, as well as females (by 52% - 53% respectively). The severity of the restrictions but also the fear of the spread of the coronavirus may be relevant to the insufficient seek of help for these groups of patients. Conclusion: Our study showed that during the pandemic period, the invasive interventions were fewer than those of 2019. However, the expected reduction of catheterizations during this two and a half months period was mitigated by the increase of inter-hospital transfers of patients with ACS from neighboring hospitals, without a catheterization laboratory.